Intervensi Keperawatan Jiwa Berbasis Komunitas dalam Meningkatkan Kemandirian Perawatan Diri dan Kualitas Hidup ODGJ - Endah Sari Purbaningsih; Muadi, Muadi; Teri Melani (Jurnal Pengabdian Ilmu Kesehatan, 2026)
People with Mental Disorders (ODGJ) often experience self-care deficits that impact personal hygiene, the ability to perform daily activities, and overall quality of life. This condition requires community-based psychiatric nursing interventions that focus not only on the patient but also involve the family as the primary support system. This activity aims to improve the independence of self-care for people with ODGJ through a community psychiatric nursing approach. The method used is descriptive, with stages of preparation, assessment, planning, implementation, and evaluation conducted through regular home visits. The interventions provided include mental health education, self-care training such as bathing, dressing, and maintaining environmental cleanliness, therapeutic communication, and family empowerment in supporting the patient. The results of the activities indicate an increase in the ability of ODGJ to maintain personal hygiene, perform daily activities independently, and increased family involvement in the care process and monitoring of the patient’s condition. However, the patient’s ability to interact socially and achieve full independence still requires ongoing support and monitoring. Community psychiatric nursing interventions have proven effective in improving the independence of self-care for people with ODGJ and strengthening family support to sustainably improve the patient’s quality of life.